Report proposed upgarding Tanjung Dawai Sea Food Arcade at Sungai Petani, Kedah Darul Aman for Majlis Perbandaran Sungai Petani (M.P.S.P) / Mohd Firdaus Shamsudin - Shamsudin, Mohd Firdaus (Faculty of Architecture, Planning and Surveying, 2004)
Since our independent from the British colonials in 1957, we had grown rapidly in terms of developing this country in educational level, economic status, and public infrastructures aspects. Through the democratic system that allows the people to voice out their opinion Malaysian are able to communicate with the government for a good cause. The state government is responsible to all the development in each state make it much easier to develop all the rural area in Malaysia to share the prosperity together in the diverse culture environment. Due to the visions of our ex prime minister Tun Dr. Mahathir that wanted Malaysia to develop as a develop country by the year 2020. in order to archive this visions we might eager to construct new places of interest that can profit us more but at same time we forget that we also have lots of old buildings that have the potentials to profit us for a long time. New develop projects is necessary but refurbishing the old building that will benefit us is essentials towards developing and preserving the heritage of our culture. Therefore, for this project there are three method of research have been done to accommodate the need of the project that is to respect the surrounding environment and to make the project more interesting and able profit the country also increase the quality of life of the villagers.